2016
DOI: 10.1111/iwj.12649
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, multicentre, open‐label, single‐arm clinical trial for treatment of chronic complex diabetic foot wounds with exposed tendon and/or bone: positive clinical outcomes of viable cryopreserved human placental membrane

Abstract: Complex diabetic foot ulcers (DFUs) with exposed tendon or bone remain a challenge. They are more susceptible to complications such as infection and amputation and require treatments that promote rapid development of granulation tissue and, ultimately, reepithelialisation. The clinical effectiveness of viable cryopreserved human placental membrane (vCHPM) for DFUs has been established in a level 1 trial. However, complex wounds with exposed deeper structures are typically excluded from randomised controlled cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
50
1
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 41 publications
4
50
1
4
Order By: Relevance
“…The results of this retrospective cohort study are similar to retrospective cohort studies and prospective RCTs in patients with DFUs . Almost 60% of DFUs achieved closure with a median time to closure of 42.0 days with a median of 4 applications of vCPM.…”
Section: Discussionsupporting
confidence: 76%
“…The results of this retrospective cohort study are similar to retrospective cohort studies and prospective RCTs in patients with DFUs . Almost 60% of DFUs achieved closure with a median time to closure of 42.0 days with a median of 4 applications of vCPM.…”
Section: Discussionsupporting
confidence: 76%
“…The chorionic membrane is jelly-like that allows easy application into a narrow fistula's tract. Our hypothesis is that the soft chorionic graft fills fistula and supports formation of granulation tissue followed by the closure of the fistula similar as it was reported for complex leg wounds [31]. …”
Section: Discussionsupporting
confidence: 70%
“…Retrospective and prospective clinical studies have demonstrated benefits of Grafix Prime for wounds of various etiology including venous stasis ulcers, diabetic foot ulcers, pressure ulcers, and surgical dehiscence [29, 30]. The clinical effectiveness of viable cryopreserved chorionic membrane for complex wounds with exposed tendon and/or bone has been demonstrated in a recent prospective multicenter clinical trial [31]. In this study 96.3% patients achieved 100% granulation of the wound bed, and 59.3% of patients completely closed their wounds [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scientific studies show that vCPM retain all components and properties of native fresh tissue 9. Retrospective and prospective clinical studies report positive outcomes with vCPM in management of acute and chronic wounds including complex wounds with exposed bone, tendon, or joint capsule 10, 11, 12, 13. Previously we reported vCPM use for outpatient management of two complex burn wounds that prevented potential amputation in one patient and formation of finger contracture in the second patient.…”
Section: Discussionmentioning
confidence: 99%